EFEKTIVITAS PENGGUNAAN MEDIA WORDWALL TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI DI KELAS X SMA - Sufi, Ade Afilia; Asriati, Nuraini; Syahrudin, Husni (Universitas Tanjungpura, 2024)
This research aims to analyze the effectiveness of the Wordwall learning media in improving learning outcomes in economics subjects for class X students at SMA Negeri 8 Pontianak. The subjects of this research were 72 students consisting of 36 students from class XE and 36 students from XF. This research is an experimental research with a nonequivalent control group design. The analysis techniques used are reliability tests, normality tests and effect size tests. Based on the results of the effect size test analysis on the pretest and posttest data for the experimental group, it shows a value of 0.97, which is included in the large classification. The results of the independent sample t-test have a significance value of 0.001 0.05. This can show that there are differences in learning outcomes between before the wordwall learning media was applied and after the wordwall learning media was applied. It can be concluded that the Wordwall learning media has significant effectiveness on the learning outcomes of class X students at SMA Negeri 8 Pontianak.